2019
DOI: 10.31234/osf.io/vjkdf
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Early Phonological Neural Specialization Predicts Later Growth in Word Reading Skills

Abstract: According to the Interactive Specialization Theory, cognitive skill development is facilitated by a process of neural specialization. In line with this theory, the current study investigated whether neural specialization for phonological and semantic processing at 5-to-6 years old was predictive of growth in word reading skills from 5-to-8 years old. Specifically, four regression models were estimated in which reading growth was predicted from: (1) an intercept-only model, (2) measures of semantic and phonolog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
1

Year Published

2022
2022
2022
2022

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 31 publications
1
3
1
Order By: Relevance
“…In the pre-registered analyses, we related functional connectivity during all lexical conditions with standardized measures of reading. Contrary to the prior literature showing moderate to strong associations between phonological brain systems and word reading skills (e.g., Jasinska et al, 2020;Wang et al, 2013;Wang et al, 2020Yamasaki et al, 2021;Yu et al, 2018), we only found weak (and statistically unreliable) correlations between connectivity in the dorsal pathway and children's word reading skills. To our surprise, this weak correlation was also evident in our first exploratory analyses which examined connectivity using a task contrast of targeted conditions, (O+P+ & O-P-) > fixation for the rhyming task and (strongly related & unrelated) > fixation for the semantic task.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…In the pre-registered analyses, we related functional connectivity during all lexical conditions with standardized measures of reading. Contrary to the prior literature showing moderate to strong associations between phonological brain systems and word reading skills (e.g., Jasinska et al, 2020;Wang et al, 2013;Wang et al, 2020Yamasaki et al, 2021;Yu et al, 2018), we only found weak (and statistically unreliable) correlations between connectivity in the dorsal pathway and children's word reading skills. To our surprise, this weak correlation was also evident in our first exploratory analyses which examined connectivity using a task contrast of targeted conditions, (O+P+ & O-P-) > fixation for the rhyming task and (strongly related & unrelated) > fixation for the semantic task.…”
Section: Discussioncontrasting
confidence: 99%
“…Phonological specialization in the left STG is evident in children by age five (e.g., Mathur et al, 2020;Weiss, Cweigenberg, & Booth, 2018;Yamasaki et al, 2021), whereas specialization in the dorsal IFG is thought to develop later around age seven (e.g., Wang, Yamasaki, Weiss, & Booth, 2021;Yamasaki et al, 2021). Notably, the engagement of this dorsal fronto-temporal pathway during phonological processing is predictive of children's word reading skills throughout reading development (Wang et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Further, letter name and sound knowledge at 5-years correlated with estimated myelin density in the left arcuate and the left and right ILF at 26-months. These results extend previous studies indicating that brain structure and function in the left dorsal pathways in 5-year-olds predict later reading skills including letter-word identification (Wang et al, 2020;Yamasaki et al, 2021), phonological awareness (Yu et al, 2018), cross-modal audio-visual processing Booth, 2014, 2015), and word and pseudoword reading (Van Der Auwera et al, 2021). The current study indicates similar correlations between earlier left dorsal white matter structure and 5-yearolds' letter names and sound knowledge, suggesting that these relations already exist in toddlers, long before the onset of reading instruction, and support reading acquisition.…”
Section: Brain-behavior Correlationssupporting
confidence: 89%
“…The left AF and SLF have previously been found to be related to the development of expressive and receptive language skills (O'Muircheartaigh et al, 2014;Deoni et al, 2016;Salvan et al, 2017;Swanson et al, 2017;Romeo et al, 2018aRomeo et al, , 2021Girault et al, 2019b;Sket et al, 2019), and emergent literacy skills (Lebel and Beaulieu, 2009;Yeatman et al, 2011;Saygin et al, 2013;Yu et al, 2018;Wang et al, 2020;Van Der Auwera et al, 2021;Yamasaki et al, 2021). Furthermore, previous studies have shown that the left AF correlates with parent-child conversational turns in 4-6year-olds (Romeo et al, 2018a(Romeo et al, ,b, 2021, and that left dorsal activation and plasticity mediate the relations between parentchild conversational turns and comprehensive language skills (Romeo et al, 2018a).…”
Section: Mediation Analysismentioning
confidence: 92%
See 1 more Smart Citation